Мои бельгийские литературные встречи - Денисов, Ю.С. (Культура народов Причерноморья, 2014)
Данная статья представляет собой воспоминания автора о своей языковой стажировке в
Бельгии и о знакомстве с бельгийским писателем Анри Корнелюсом, его жизни и творчестве. Также
автор рассказывает о, пожалуй, главном произведении Корнелюса, романе “Вельзевул”, раскрывает его
содержание, основную идею и выделяет проблемы, поднятые в тексте. Этот роман чрезвычайно
интересен и, в то же время, малоизучен в нашей стране. В этом и заключается научная новизна
работы. Дана стаття являє собою спогади автора про своє мовне стажування в Бельгії та про
знайомство з бельгійським письменником Анрі Корнелюсом, про його життя та творчість . Також
автор розповідає про, мабуть, головний твiр Корнелюса, роман "Вельзевул", розкриває його зміст,
основну ідею і виділяє проблеми, підняті в тексті. Цей роман надзвичайно цікавий і, в той самий час,
маловивчений в нашій країні. У цьому і полягає наукова новизна цієї роботи. This article is the author's memories of his language training in Belgium and of the meeting with the
Belgian writer Henri Cornelus, of his life and his works. The author visited Belgium in 1978 as a member of
Soviet university delegation and met Cornelus on the literature exhibition where he struck up an acquaintance
with him. The author also talks about, perhaps, the main Corneluse's work, the novel "Belzebuth", characterized
as an anti-racist novel. This story is about an Algeria origin young man Achmed, who clashed with a French
society. He had a terrible childhood, then– a terrible life. He was alone in that ugly, small-minded society. The
author also reveals the main idea and identifies the problems raised in the text. Problems of relationship
between emigrants and natives. This novel is very interesting and, at the same time, little-studied in our country.
So this is the scientific novelty of this work. Besides, the author touches upon another Cornelus work, his book
'''Ceux de la dure patience'', in which H. Cornelus describes the difficult life of fishermen, their fates and brave
characters. In the end of the article, the author speaks about Corneluse's heritage. After his death, the
international literary prize, named for his honour, was instituted.